THE EFFECT OF PSIDIUM GUAJAVA LEAVES EXTRACTS AND THEIR EFFECTIVE COMPOUND AGAINST LEISHMANIA INFANTUM - A. Taha, Sahar (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: This study aims to evaluate the anti-leishmanial activity of aqueous and alcoholic extracts of Psidium guajava L. against Leishmania infantum. Additionally, it involves screening the phenolic and flavonoid compounds in the extracts using High-Performance Liquid Chromatography (HPLC). Methods: Standardized methods were employed to prepare aqueous and alcoholic extracts of Psidium guajava L. In vitro assays tested the inhibitory effect of these extracts on the growth of Leishmania infantum promastigotes, with the IC50 values determined. HPLC analysis identified flavonoids and phenolic compounds in the alcoholic extract. Data analysis explored the correlation between compound concentration and anti-leishmanial activity. Results: : The aqueous and alcoholic extracts exhibited significant inhibitory effects on Leishmania infantum promastigote growth. The IC50 value for the aqueous extract was 0.25 mg/mL, while the alcoholic extract showed a slightly higher potency with an IC50 of 0.23 mg/mL. HPLC analysis confirmed the presence of phenolic and flavonoid compounds in the alcoholic extract, which are likely responsible for the observed anti-leishmanial activity. Novelty: This study demonstrates the anti-leishmanial potential of Psidium guajava L., highlighting its aqueous and alcoholic extracts as promising candidates for further investigation. The identification of specific phenolic and flavonoid compounds provides insights into the bioactive components contributing to the inhibitory effects.